Barriers of Biodiesel Adoption by Transportation Companies: A Case of Malaysian Transportation Industry - Zailani, Suhaiza; Iranmanesh, Mohammad; Sean Hyun, Sunghyup; Ali, Mohd (MDPI, 2019)
The need to develop an alternative fuel to fossil fuel is growing day by day, especially for the transportation industry, as the supply of fossil fuels is limited and is depleting at a rapid rate. One available resource that has emerged recently is biodiesel. However, the usage of biodiesel is very low among transportation companies. An investigation into the barriers of adopting biodiesel by transportation companies is the focus of the present study. A survey of 147 transportation companies in Malaysia was undertaken, and the data gathered were analyzed using partial least squares technique. Lack of government support, lack of environmental-commercial benefits, and lack of competitive pressure were found to be the barriers to biodiesel adoption. The results also indicated that differentiation strategy moderates the impact of lack of government support, lack of customer demand, lack of environmental-commercial benefits and lack of competitive pressure on biodiesel adoption. The results of this study could benefit policy makers by providing them key focus areas in which they can modify their strategies to actively and successfully promote the use of biodiesel among transportation companies in developing countries.